Тенденции развития автомобильных систем зажигания - Корытченко, Константин Владимирович; Волонцевич, Дмитрий Олегович; Ковцур, Ю. В. (НТУ "ХПИ", 2010)
Здійснено аналіз напрямків розвитку автомобільних систем запалювання виходячи з принципу їх роботи. Розглянуті схемні рішення, що застосовуються у системах запалення, з описом радіо елементної бази, що застосовувалась у дослідженнях. Надано дані щодо впливу параметрів систем запалювання з сильно струмовим розрядом на характеристики двигуна.

The analysis of tendency for the motor-car ignition systems development is made taking into account operation principles of the systems. It is considered circuit designs of the ignition systems. Description of radio electronic components of the experimental electrical circuit is presented. Results of influence of the circuit parameters of the ignition system forming a high-current discharge on engine features are given.
Keywords: развитие автомобилей; двигатели внутреннего сгорания; мощность двигателя; энергия разряда; объем воспламенения; турбулизация пламени